Cost Contingency Estimation in Public Projects in the Construction Digitalisation Era: A Case of Vietnam - Nguyen, Nhan T.T.; Dang, Mai; Nguyen, The-Quan (International Journal of Sustainable Construction Engineering and Technology, 2022)
Construction projects, in nature, are complex and dynamic, therefore, when estimating the project budget, there should be a budget set aside, called â€œcontingencyâ€ for dealing with changes in the project internally and externally. This paper, used a case study of a public hospital in Vietnam, discussed the estimation of cost contingencies in the preliminary feasibility study and feasibility study stages. Cost contingencies estimation using the construction investment rates have low accuracy, therefore, have been adjusted and re-allocated through out the stages. Additional data is needed for improving the accuracy of the contingency estimation. This approach is facilitated in the construction digitalisation era, especially with the issuance of Circular 12/2019/TT-BXD guiding the development and management of the systems of databases on cost norms, prices and price indexes. Historical data can increase the accuracy of the estimation of costs for construction consultancy services, including BIM services, which are currently estimated by predefined rates based on construction and equipment costs.